Study of Modern Radio Spectrum Management Mode - Bo Feng (Dianxin kexue, 2013)
Modern radio spectrum management modes were introduced briefly,analyzed and compared.Recommendation on our country's future radio spectrum management was put forward. Spectrum resources management mode should be a dynamic market-based approach, which combines command and control model, property right mode, commons or unlicensed mode and intelligent mode.